The link between anxiety and assessment of body attitudes and body size estimation in anorexia nervosa. Issue 1 (16th March 2021) - Hasenack, Birgit; Sternheim, Lot; Bijsterbosch, Jojanneke; Keizer, Anouk
Although body size estimation (BSE) tasks are frequently used to investigate distorted body representation in anorexia nervosa (AN), the link between anxiety and task performance has been overlooked. To investigate this, 30 female healthy controls (HCs) and 29 female AN patients completed two body attitude questionnaires and three BSE tasks (the Visual Estimation Task, the Tactile Estimation Task and the Hoop Task). Participants completed two body attitude questionnaires and three BSE tasks; the Visual Estimation Task, the Tactile Estimation Task, and the Hoop Task. The STAI-6 was administered before and after each body-related task to assess state anxiety. Results showed that state anxiety levels increased significantly more in AN patients than in HC after completing each task. Thus, performance of AN patients on BSE and other body-related tasks might not just indicate the (mis)perception of their body but also co-occur with increased state anxiety. This has implications for the interpretation of these tasks and for furthering our understanding of the mechanisms that underlie distorted body image in AN.